The Effect of Inflation, Exchange Rate, Labor and Money Supply on The Manufacturing Industry Sector in Indonesia 2011 – 2020 - Amri, Faizal (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
The manufacturing industry is the main supporting sector for the economy, considering its enormous contribution to Indonesia's national GDP compared to other sectors. However, the economic problems lately have resulted in a decline in Indonesia's economic conditions, which is marked by a reduction in national GDP and a decrease in the output of the Indonesian manufacturing industry sector. Thus, this study aims to analyze the effect of the complex variables in the current economy, namely inflation, exchange rates, labor, and the money supply, on the manufacturing industry sector in Indonesia in the long and short term. This study uses the ECM (error correction model) method in empirical testing. The data used is secondary time series data (quarterly) starting from 2011:Q1 – 2020:Q4; the data obtained comes from the Central Statistics Agency, Bank Indonesia, and the Ministry of Trade of the Republic of Indonesia. This study uses the Eviews10 application as an analytical tool. The analysis results conducted in this study show that the exchange rate and labor have a positive and significant influence on the manufacturing industry sector in the long and short term. The money supply has a positive and significant effect on the manufacturing industry sector in the long term only. Meanwhile, inflation has a negative but not significant effect both in the long term and short term. Of these critical variables, labor has the most crucial influence on the manufacturing industry sector. Therefore, the government needs to pay attention to policies related to labor as the main factor in increasing the output of the manufacturing industry.